Audio Media in Islamic Religious Education Learning - Hafid Muslih; Gilang Sukma Permana (Program Studi Pendidikan Agama Islam, Universitas Muhammadiyah Bandung, 2024)
The learning process is the process of communication between teachers and students through verbal language as the main medium for delivering learning material. In these conditions, the learning process depends on the teacher as a learning resource. However, not all teaching materials can be presented directly by the teacher. To learn about the life of living creatures on the seabed, it is not possible for the teacher to guide students directly to the bottom of the ocean, or to divide the human chest just to learn how the organs of the human body work. However, the teacher can use various kinds of tools in delivering learning material. This learning aid is meant by media or teaching aids. In PAI learning, so that the learning material provided is more easily understood by students, it takes media to help the delivery process. Through the media (tools), it is expected that the same perception will occur between teachers and students. Moreover, Islamic Education is education that is very important for human life, especially in achieving inner peace and mental health in general. Audio media can be used as an alternative to learning PAI.